2007
DOI: 10.1007/s10549-007-9538-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary animal-derived iron and fat intake and breast cancer risk in the Shanghai Breast Cancer Study

Abstract: A high intake of animal-derived (heme) iron may be associated with an increased risk of primary breast cancer in Chinese women, and saturated and mono-unsaturated fats that are also derived from animal sources may augment this effect. Combined reductions in animal-derived iron and fat consumption have the potential to reduce breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 42 publications
1
61
2
Order By: Relevance
“…To date, dietary intake of iron is assumed to be an important source for elevated iron store. For example, a case-control survey of 3452 breast cancer patients and 3474 age-frequency-matched healthy controls in China showed that intake of meat-derived hemeiron increased the risk of breast cancer in Chinese women [32]. Similar observations were found for cancer patients in the US [33].…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthmentioning
confidence: 62%
“…To date, dietary intake of iron is assumed to be an important source for elevated iron store. For example, a case-control survey of 3452 breast cancer patients and 3474 age-frequency-matched healthy controls in China showed that intake of meat-derived hemeiron increased the risk of breast cancer in Chinese women [32]. Similar observations were found for cancer patients in the US [33].…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthmentioning
confidence: 62%
“…A large number of studies have delineated the considerable contribution altered iron metabolism to tumor development (Bystrom et al, 2012;Richardson et al, 2009;Torti and Torti, 2011). For example, case-control surveys of breast cancer patients revealed that intake of meat-derived heme-iron increased the risk of breast cancer (Ferrucci et al, 2009;Kallianpur et al, 2008). Therefore, our current study provides an additional novel mechanism by which PCBs instigate cancer progression through disturbing systemic iron homeostasis.…”
Section: Resultsmentioning
confidence: 81%
“…Articles accepted for analysis (n = 33) DOI:http://dx.doi.org/10.7314/APJCP.2014.15.3.1291 Association between Dietary Factors andBreast Cancer Risk among Chinese Females: Meta-analysis Li et al, 2006;Shen et al, 2006;Zhu et al, 2006;Wang, 2007;Kallianpur et al, 2008;Ren, 2008;Rong et al, 2008;Wang et al, 2008;Fang et al, 2009;Zhang et al, 2009;Zhou et al, 2009;Cheng et al, 2010;Guo et al, 2010;Zheng et al, 2010;Wang et al, 2011;Liang, 2012;Yao et al, 2012;Yu et al, 2012;Zhang et al, 2012;Bo et al, 2013;Luo et al, 2013). Four duplicate publications were excluded (Wang, 2000;Zhang et al, 2003;Zou et al, 2003;Fang et al, 2009).…”
Section: Resultsmentioning
confidence: 99%